Gêneros audiovisuais digitais na criação de um modelo estratégico de produção e veiculação de vídeos para a internet. - Melo Segundo, Carlos Alberto Henrique de (2021)
This technical report presents, through the study and cataloging of what they are and what are some of the main digital audiovisual genres prevalent on the internet and how to use them in the creation of a strategic model of production and placement of videos for digital social media. The transformation of language, the change of habits and the speed with which digital social networks emerge and fall into obsolescence, which are the main platforms for distributing audiovisual content on the internet, in addition to understanding the way in which we engage and share the content that is offered to us at all times are part of this research. To achieve this objective, we proceeded with a bibliographic research, followed by a practical phase in which videos were produced within our framework proposal. We are based on the thoughts of Vieira (2018) on how these platforms transform the business model of communication companies, Berger (2014) on the way content spreads over the internet and Aronchi (2003) on the need for entertainment as a resource. of audiovisual production. In this work, 17 videos were produced for two micro companies, a barber shop and a pediatric dentistry clinic, within a previously established plan, with the purpose of presenting a framework that can be used and replicated by any professional or researcher in the area. As a result, we could see that the digital genres native to these platforms work as the most appropriate strategy for the production and broadcasting of audiovisual content on the internet.